2020
DOI: 10.17116/hirurgia202002113
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy-assisted surgical treatment of carotid artery kinking

Abstract: Цель исследования-оценка результатов хирургической коррекции дистальных извитостей внутренней сонной артерии с применением эндоскопии. Материал и методы. С 1 января по 31 декабря 2018 г. на базе НИИ СП им. Н.В. Склифосовского (Москва) и Республиканской клинической больницы г. Нальчика проведено хирургическое лечение 11 пациентов с высокой патологической извитостью внутренней сонной артерии с применением эндоскопической ассистенции. Результаты и обсуждение. Интраоперационных осложнений не зафиксировано (объемна… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Carotid surgery might be performed in other but selected symptomatic patients (3). ere are reported cases with pulsatile tinnitus in which carotid surgery of kinking produced good clinical outcome (13,14). Ballotta et al showed that carotid surgery for symptomatic (causing cerebral ischemic symptoms) carotid kinking is superior in preventing stroke in comparison to the best medical therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid surgery might be performed in other but selected symptomatic patients (3). ere are reported cases with pulsatile tinnitus in which carotid surgery of kinking produced good clinical outcome (13,14). Ballotta et al showed that carotid surgery for symptomatic (causing cerebral ischemic symptoms) carotid kinking is superior in preventing stroke in comparison to the best medical therapy (15).…”
Section: Discussionmentioning
confidence: 99%